Silent Trauma: Unraveling the Legal Silence on Marital Rape in India - Chatterjee, Pyali; Roy , RN (Journal of Indian Academy of Forensic Medicine, 2024)
Unveiling the entrenched patriarchal norms, this article delves into the glaring issue of marital rape in India, exploring the repercussions of the continued legal silence on victims’ mental trauma. Despite recommendations from the Justice J. S. Verma Committee, neither the Rape Law nor The Bharatiya Nyaya Sanhita, 2023 addresses marital rape. The absence of legal clarity leaves wives over 18 without recourse. The article sheds light on the underreported prevalence of marital violence, its impact on mental health, and the urgent need for legal and medical intervention. The silence around these issues perpetuates a cycle of suffering, emphasizing the imperative for legal reform and societal awareness.